Endoscopic Third Ventriculostomy for Hydrocephalus Secondary to Extraventricular Obstruction in Thalamic Hemorrhage: A Case Series. Issue 4 (4th May 2020) - Zeineddine, Hussein A; Dono, Antonio; Kitagawa, Ryan; Savitz, Sean I; Choi, Huimahn Alex; Chang, Tiffany R; Ballester, Leomar Y; Esquenazi, Yoshua
Abstract: BACKGROUND: Intracranial hemorrhage carries significant morbidity and mortality, particularly if associated with hydrocephalus . Management of hydrocephalus includes temporary external ventricular drainage, with or without shunting. Thalamic location is an independent predictor of mortality and increases the likelihood of shunt dependence. OBJECTIVE: To determine whether endoscopic third ventriculostomy (ETV) can avoid the need for shunt placement and expedite recovery. METHODS: We prospectively identified thalamic intracranial hemorrhage patients who developed acute hydrocephalus requiring cerebrospinal fluid diversion by extraventricular drain placement from November 2017 to February 2019. Patients who failed an extraventricular drain clamping trial were then evaluated for eligibility for an ETV procedure. Patients who underwent ETV were then followed up for the development of hydrocephalus, need for shunting, and length of stay in the intensive care unit. RESULTS: Eight patients (7 males, 1 female) were prospectively enrolled. All patients underwent an ETV successfully. None of the patients required shunting. ETV was performed despite the presence of other factors that would have prevented shunt placement, including fever, leukocytosis, and gastrostomy tube placement. Seven patients who underwent ETV were evaluated at 3-mo follow-up and did not require shunting. CONCLUSION: ETV is a safe and effective technique for the management of hydrocephalus resulting from an extraventricular obstruction in thalamic hemorrhage. It can avoid the need for permanent shunting in this patient population. Larger studies should be conducted to validate and further analyze this intervention. Graphical Abstract: